Physio-pathological effects of N6-methyladenosine and its therapeutic implications in leukemia - Wei-Wei Liu; Hao Wang; Xiao-Yu Zhu (BMC, 2022)
Abstract N6-methyladenosine (m6A), the most prevalent epigenetic modification of RNA in mammals, has become a hot topic throughout recent years. m6A is involved with every links of the RNA fate, including RNA splicing, nuclear export, translation and stability. Due to the reversible and dynamic regulatory network composed of 'writers' (methylase), 'erasers' (demethylase) and 'readers' (m6A binding proteins), m6A has been deemed as an essential modulator in vast physiological and pathological processes. Previous studies have shown that aberrant expression and dysfunction of these regulators are implicated in diverse tumors, exemplified by hematological malignancies. However, we should hold a dialectic perspective towards the influence of m6A modification on leukemogenesis. Given that m6A itself is neither pro-oncogenic nor anti-oncogenic, whether the modifications promote hematological homeostasis or malignancies occurrence and progression is dependent on the specific targets it regulates. Ample evidence supports the role of m6A in maintaining normal hematopoiesis and leukemogenesis, thereby highlighting the therapeutic potential of intervention in m6A modification process for battling leukemia. In this review, we introduce the advances of m6A modification and summarize the biological functions of m6A in RNA metabolism. Then we discuss the significance of several well-studied m6A regulators in modulating normal and malignant hematopoiesis, with focus on the therapeutic potentials of targeting these regulators for battling hematopoietic malignancies.